Interactive E-Modules in Life Science to Foster Scientific Literacy and Process Skills in Early Childhood - Salsabilla Putri Diana Edison; Delfi Eliza; Yaswinda Yaswinda; Rakimahwati Rakimahwati (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Childhood is a crucial period for cognitive, social, and emotional development. Therefore, science literacy and science process skills need to be stimulated from an early age. However, science learning in early childhood education still faces challenges such as limited interactive learning media, low teacher confidence in teaching science concepts, and a lack of developmentally appropriate learning resources. This study aims to develop and evaluate an interactive e-module based on life science to enhance scientific literacy and science process skills among young children. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects involved teachers and children aged 5–6 years in early childhood education settings. Data were collected through expert validation sheets, teacher response questionnaires, and observation sheets of children's learning activities. The data were analyzed using descriptive quantitative analysis to determine the validity, practicality, and effectiveness of the developed product. The results indicate that the interactive e-module demonstrates very high levels of validity, practicality, and effectiveness. The use of the e-module increases children's engagement in science learning and assists teachers in designing more systematic, contextual, and engaging learning activities. The findings imply that multimedia-based interactive e-modules can serve as an innovative learning resource to support meaningful science learning and strengthen scientific literacy and science process skills in early childhood education.